Stimulating endogenous cardiac repair - Finan, Amanda; Richard, Sylvain (Frontiers in Cell and Developmental Biology, 2015)
The healthy adult heart has a low turnover of cardiac myocytes. The renewal capacity, however, is augmented after cardiac injury. Participants in cardiac regeneration include cardiac myocytes themselves, cardiac progenitor cells, and peripheral stem cells, particularly from the bone marrow compartment. Cardiac progenitor cells and bone marrow stem cells are augmented after cardiac injury, migrate to the myocardium, and support regeneration. Depletion studies of these populations have demonstrated their necessary role in cardiac repair. However, the potential of these cells to completely regenerate the heart is limited. Efforts are now being focused on ways to augment these natural pathways to improve cardiac healing, primarily after ischemic injury but in other cardiac pathologies as well. Cell and gene therapy or pharmacological interventions are proposed mechanisms. Cell therapy has demonstrated modest results and has passed into clinical trials. However, the beneficial effects of cell therapy have primarily been their ability to produce paracrine effects on the cardiac tissue and recruit endogenous stem cell populations as opposed to direct cardiac regeneration. Gene therapy efforts have focused on prolonging or reactivating natural signaling pathways. Positive results have been demonstrated to activate the endogenous stem cell populations and are currently being tested in clinical trials. A potential new avenue may be to refine pharmacological treatments that are currently in place in the clinic. Evidence is mounting that drugs such as statins or beta blockers may alter endogenous stem cell activity. Understanding the effects of these drugs on stem cell repair while keeping in mind their primary function may strike a balance in myocardial healing. To maximize endogenous cardiac regeneration,a combination of these approaches couldameliorate the overall repair process to incorporate the participation ofmultiple cell players.